2020
DOI: 10.1002/joc.6727
|View full text |Cite
|
Sign up to set email alerts
|

Increasing summer precipitation in arid Central Asia linked to the weakening of the East Asian summer monsoon in the recent decades

Abstract: It is generally believed that water vapour from the North Atlantic transported by the mid‐latitude westerlies dominates precipitation variations in arid Central Asia, where monsoonal water vapour source is beyond the reach. This study reexamines water vapour sources for arid Central Asia based on daily reanalysis data. The results reveal two water vapour sources for arid Central Asia: the westerly water vapour transport from the North Atlantic and the monsoonal water vapour transport from the tropical Indian O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 51 publications
0
59
0
Order By: Relevance
“…The thermodynamic component of the moisture convergence is induced by the increased specific humidity associated with enhanced evaporation (Peng & Zhou, 2017; Trenberth, 2005; Wu et al., 2019), while its dynamic component is dominated by an anomalous cyclone over central Asia that is associated with a significant southward displacement of the Asian subtropical westerly jet (Peng & Zhou, 2017). Additionally, the increasing precipitation (and extreme precipitation) in ANC may also be closely related to the weakened East Asian summer monsoon that promotes the westward transport of water vapor from the Indian and Pacific Oceans to ANC by intensifying the westward extension of the western Pacific subtropical high and increasing Mongolian anticyclonic activities (C. Chen et al., 2020; F. Chen et al., 2021). It is noted that the rationale for putting the synoptic diagnostics and wetting trends together in ANC is still not fully understood and warrant in‐depth investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The thermodynamic component of the moisture convergence is induced by the increased specific humidity associated with enhanced evaporation (Peng & Zhou, 2017; Trenberth, 2005; Wu et al., 2019), while its dynamic component is dominated by an anomalous cyclone over central Asia that is associated with a significant southward displacement of the Asian subtropical westerly jet (Peng & Zhou, 2017). Additionally, the increasing precipitation (and extreme precipitation) in ANC may also be closely related to the weakened East Asian summer monsoon that promotes the westward transport of water vapor from the Indian and Pacific Oceans to ANC by intensifying the westward extension of the western Pacific subtropical high and increasing Mongolian anticyclonic activities (C. Chen et al., 2020; F. Chen et al., 2021). It is noted that the rationale for putting the synoptic diagnostics and wetting trends together in ANC is still not fully understood and warrant in‐depth investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The change in westerly circulation may be the main factor affecting the evolution of precipitation in the arid region of Central Asia (Chen et al, 2011). Chen et al (2021) also found that the East Asian summer monsoon has experienced a persistent weakening trend since 1958, causing an increasing contribution of monsoonal water vapor transport and enhancing summer precipitation in Central Asia. Besides these factors, Peng et al (2018) also found that human-induced warming increased the specific humidity over all of Central Asia, increasing (decreasing) the precipitation over eastern (western) Central Asia.…”
Section: Introductionmentioning
confidence: 89%
“…Research integrating ice cores, stalagmites, and lake records reveals that the temperature of Northwest China warmed rapidly at the beginning of the 1950s (Figure 6D; Ding, 2010), which is consistent with the rapid warming trend in China (Ge et al, 2015). With rising temperatures, precipitation in the arid region of Northwest China has increased in recent decades (Chen et al, 2020;Liu et al, 2021). The reconstructed precipitation from tree rings shows that the annual precipitation began to increase at the beginning of the 1950s on the southern margin of the desert and the northeastern Tibetan Plateau (Figure 6C; Yang et al, 2010;Yang et al, 2014;Zhang et al, 2015;Liu et al, 2021).…”
Section: The Factors Influencing Lake Evolutionmentioning
confidence: 97%